2021
DOI: 10.2217/pmt-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Inflammation with Hematological Parameters in Patients with Migraine and Tension-Type Headache: A Prospective Study from A Tertiary Care Center

Abstract: Aim: To investigate the role of inflammatory markers in patients with an acute headache attack. Materials & methods: This prospective controlled observational study comprised 150 subjects (migraine with aura [MA] n = 51, migraine without aura [MO] n = 51, tension-type headache n = 48, healthy controls n = 80). White blood cells (WBC), neutrophil, lymphocyte and platelet counts, mean platelet volume, neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio were documented. Results: MA and MO constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…In summary, some of the studies reported a higher neutrophil [ 4 – 6 ], platelet [ 5 ] counts, and lower lymphocyte counts [ 4 , 5 ] in migraine patients during the ictal period compared to healthy controls. However, these findings were not replicated by other studies [ 5 7 , 9 ]. In addition, previous studies were hospital-based and conducted within a selected group of participants suffering from migraine attacks severe enough to warrant admission to a hospital.…”
Section: Discussioncontrasting
confidence: 82%
“…In summary, some of the studies reported a higher neutrophil [ 4 – 6 ], platelet [ 5 ] counts, and lower lymphocyte counts [ 4 , 5 ] in migraine patients during the ictal period compared to healthy controls. However, these findings were not replicated by other studies [ 5 7 , 9 ]. In addition, previous studies were hospital-based and conducted within a selected group of participants suffering from migraine attacks severe enough to warrant admission to a hospital.…”
Section: Discussioncontrasting
confidence: 82%
“…The number of studies examining TTH and peripheral inflammation is limited [6,7]. The effects of systemic inflammation on tension-type headache are not clearly known.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with these previous studies. By contrast, a prospective controlled observational study showed that, although high in headache patients, there were no significant differences in the NLR among migraine, TTH, and controls [ 22 ]. Our nMH group included patients with diagnostic codes for TTH or non-specific headache; all types of migraine were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, systemic inflammation parameters, including the NLR, PLR, and CRP level, are significantly elevated in chronic TTH patients [ 21 ]. However, in a prospective study that investigated the roles of inflammatory markers in migraine and TTH patients during acute headache attack, the NLR did not show a significant difference between groups [ 22 ].…”
Section: Introductionmentioning
confidence: 99%